The Sonic Hedgehog signaling pathway regulates inferior alveolar nerve regeneration. (3rd April 2018) - Yamada, Yurie; Ohazama, Atsushi; Maeda, Takeyasu; Seo, Kenji
Highlights: The transection of the IAN induced the activation of Shh signaling. An inhibition of Shh signaling led to disturbance of axon regeneration. Shh signaling controls macrophage recruitment and myelin degradation. Abstract: Activation of Shh signaling is known to be observed following injury of the peripheral nerves such as the sciatic nerve. However, the precise role of Shh signaling during peripheral nerve regeneration is not fully understood. The inferior alveolar nerve (IAN) is most commonly injured during oral surgery. Unlike the sciatic nerve, the IAN is isolated from other craniofacial tissues, as it resides in a long bony canal within the mandible. The IAN is thus an excellent experimental model for investigating peripheral nerve regeneration. In this study, the role of Shh signaling in peripheral nerve regeneration was investigated using the mouse IAN transection model. During regeneration, Shh signaling was activated within the entire distal region of the IAN and proximal stumps. Inhibition of Shh signaling by cyclopamine application at the transection site led to abnormal axon growth in random directions, a reduced number of macrophages, and an increase in myelin debris within the distal region. Shh signaling is thus involved in peripheral nerve regeneration via the regulation of myelin degradation.